Do i know you? eaudiobook - Wibberley, Emily (Penguin Audio, 2023)
One of.. Amazon's Best Romances of January · Buzzfeed's Romance Books To Look Out For In 2023 When a couple starts to feel like they’re married to a stranger, a flirtatious game of pretend becomes the spark they need to reignite their relationship. Eliza and Graham are anticipating an anything-but-sexy, weeklong getaway to celebrate their five-year anniversary. Nestled on the Northern California coastline, the resort prides itself on being a destination for those in love and those looking to find it. For Eliza and Graham, it might as well be a vacation with a roommate.   When a well-meaning guest mistakes Eliza and Graham for being single and introduces them at the hotel bar, they don’t correct him. Suddenly, they’re pretending to be perfect strangers and it’s unexpectedly…fun? Eliza and Graham find themselves flirting like it’s their first date, and waiting with butterflies in their stomach for the other to text back.  Everyone at the retreat can sense the electric chemistry between Eliza and Graham’s alter egos. But when their scintillating game of roleplaying ends, will they still feel the heat?